Caseload of a land-based trauma team. Issue 1 (February 2014) - Maddock, A; Donald, M
Background and aims: Pre-hospital care is provided by a variety of models worldwide. The Tayside Trauma Team responds from Ninewells Hospital in Dundee to provide a physician-led pre-hospital care service targeted primarily at trauma patients. We present a description of the functions of the team, and data detailing the clinical work of the Team over a six-month period. Methods and results: The Team was called out 35 times in six months and attended 22 incidents, some involving multiple casualties. 34 patients received treatment at the scene of an incident. Most incidents were road traffic collisions, although the team also attended falls from height, an assault and a vascular injury. Eight patients (24%) met Injury Severity Score criteria for major trauma (ISS>15). Mean time from 999 calls to Team activation was 20 (range 4–79) min; and mean time from Team dispatch to 'Team mobile' was 4.6 (2–21) min. Conclusion: The Tayside Trauma Team provides a physician-led pre-hospital care response on demand from the Scottish Ambulance Service. It provides critical care interventions at the scene of various incidents (primarily traumatic) to attempt to improve patient outcome. Response times are favourable.